Síntese de 1,2,3-triazóis 1,4,5-trissubstituídos via catálise heterogênea empregando reações em micro-ondas e fluxo contínuo - Dias, Cássio da Silva (Universidade Federal de São Carlos, 2018)
Heterocyclic compounds containing the 1,2,3-triazole nucleus have received special attention in the field of synthetic chemistry have seen that have a wide field of application in biological and material areas. In this work, a new methodology was developed through a more sustainable approach for the synthesis of 1,2,3-triazoles, employing microwave irradiation as a heating source for the 1,3-dipolar cycloaddition reaction. As dipolarophile, β-dicarbonyl compounds, commercially available and others prepared by means of transesterification reactions between methyl acetoacetate and different alcohols were used. As the dipole species, different organic azides were prepared via a diazonium salt formation reaction. The triazoles were synthesized using nanoparticles of copper oxide II as catalyst under microwave irradiation. This new protocol allowed the preparation of a broad scope of highly functionalized 1,4,5-trisubstituted 1,2,3-triazoles in the short reaction time, in good to excellent yields. At the end of the synthesis, a study was performed on the recovery of the nanocatalyst, being possible its use for up to 3 reactional cycles with good yields of triazoles. Still in the context of more sustainable methodologies, the continuous flow reactors have been successfully applied in the development of new synthetic methodologies, since the efficient transfer of heat and better mixing of the reactants, has implied a smaller amount of byproducts and high conversion rates, among other advantages. In this part of the work, a new methodology for the synthesis of 1,2,3-triazoles 1,4,5-trisubstituted was initiated, via a reaction of 1,3-dipolar cycloaddition between carbonyl substrates, and arylazides, with reactions catalyzed by molecular sieves under continuous flow regime catalysed by molecular sieves, obtaining high conversion rates in the triazoles.
Synthesis of 1,2,3-triazoles 1,4,5-trisubstituted via heterogeneous catalysis employing reactions in microwave and continuous flow
Keywords: 1,2,3-triazoles; Nanoparticles; Microwave; Continuous flow; CIENCIAS EXATAS E DA TERRA::QUIMICA